Mediating Effect of Productive Internet Usage on Perceived Rural Business Potential - Nur Adila, Latif (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study aims to find out the demographic factors affecting productive Internet usage and perceived rural business potential impact of Information and Communications Technology (ICT), as well as to investigate the mediating role of productive Internet usage in the relationship between antecedents of Internet adoption and perceived impact of ICT on rural business potential. The independent variables covered in this study are demographic factor, cultural differences factor, internal and external factors of ICT adoption. Productive Internet usage act as the mediating variable, while the perceived rural business potential impact of the ICT was the dependent variable in this study. The findings show significant differences in term of gender, generation, education level, and income on productive Internet usage. Perceived impact of ICT on rural business potential was significantly different between education level. Besides, the results indicate that productive Internet usage mediates the influence of all internal factors which includes perceived usefulness of ICT, perceived ease of use of ICT, and ICT literacy and external factors which includes facilities availability and family support on the perceived rural business potential impact of ICT. This study also found that perceived rural business potential impact of ICT was influenced by uncertainty avoidance and collectivism culture with the mediating effect of productive Internet usage. This study describes the importance of productive Internet usage in enhancing positive perception on the rural business potential impact of ICT, thus encourage Internet usage for businesses.